Kentsel Alanlarda Oluşan Isı Adası Etkisinin Kentsel Tasarım Yöntemleri İle Azaltılması: Aksaray Meydanı Örneği - Ekinci, Büşra (Fen Bilimleri Enstitüsü, 2016)
Küresel iklim değişikliği kent yaşamını gün geçtikçe daha çok olumsuz yönde etkilemektedir. Nüfus artışı, sanayileşme gibi fiziksel faktörlerin yanı sıra, üretim-tüketim biçimleri, ekonomik sistemler, yönetim ve siyaset ilişkileri gibi sosyal faktörlere bağlı olarak gelişen kentsel alanlar, küresel ısınmanın etkileri bakımından farklı araştırma alanlarınca incelenmektedir. Kentsel tasarım da, çevreye duyarlı bir kentsel gelişmenin sağlanmasında önemli uygulama ve araştırma alanlarının başında gelmektedir. Dünya nüfusunun %54’ünün yaşadığı kentsel alanlarda mevcut kaynakların koruma kullanma dengesinin sağlanması için, başta enerji tüketimi olmak üzere ekolojik parametrelerin kentsel tasarım çalışmalarında dikkate alınması gerekmektedir. Küresel iklim değişikliğinin kent yaşamı üzerindeki olumsuz etkilerinden biri de ‘’kentsel ısı adalarıdır.’’ Çevresindeki kırsal alanlara göre daha sıcak olan kentsel alanlar olarak ifade edilen kentsel ısı adalarının, yüksek düzeyde etkilerinin görüldüğü mevsimler, sıcaklık farklarının da yüksek olduğu yaz ve kış mevsimleridir. Kentsel alanlarda doğal yer örtüsünün yerini koyu renkli, kuru ve geçirimsiz yüzeylerin alması, bitki örtüsünün tahrip edilmesi, yüksek düzeyde enerji tüketilmesi, yoğun ve yüksek yapılaşma nedeniyle sıcaklıklar artarak kentsel ısı adaları oluşmaktadır. Kentlerde ısı adalarının olumsuz etkisini azaltmanın en temel faktörleri albedo (yansıtabilirlik) değerleri yüksek olan yansıtıcı yüzey kaplamalarının tercih edilmesi ve kentsel alanlarda ağaç-bitki örtüsü yüzeylerinin arttırılmasıdır. Kentsel ısı adası etkisinin değerlendirilmesinde kullanılan en önemli parametrelerden olan ve genel olarak güneş ışığını yansıtma kapasitesini ifade eden albedo, mevsimsel koşulların dışında yüzeylerin malzemelerine ve geometriye bağlı olarak değişebilir. Bu çalışmada, Aksaray Meydanı ve yakın çevresinde oluşan ısı adası etkisinin kentsel tasarım uygulamalarıyla azaltılması incelenmektedir. Çalışmanın amacı; küresel iklim değişikliğinin bir çıktısı olarak kentsel alanlarda toplumsal çevre ve yaşam kalitesini olumsuz yönde etkileyen ısı adası etkisinin azaltılmasına yönelik geliştirilen kentsel tasarım hedef ve stratejilerini belirlemektir. Tezin amacına uygun olarak geliştirilen hedefler:  kentsel alanlarda oluşan ısı adası etkisinin kentsel tasarım özellikleri üzerinden tespit edilmesi,  gelecekte yapılması planlanan tasarımların ısı adası oluşumuna etkilerinin ölçülmesi, xx  geometri ve malzeme gibi kentsel alanlarda ısı adası oluşumuna neden olan faktörler göz önünde bulundurularak, ısı adası etkisini azaltmaya yönelik kentsel tasarım stratejilerinin geliştirilmesidir. Belirtilen bu amaç ve hedefleri gerçekleştirmek üzere Aksaray Meydanı ve yakın çevresini kapsayan 26,85 hektarlık alan çalışma alanı olarak belirlenmiştir. Aksaray, İstanbul’un kent içi ulaşımında düğüm noktası olmasının da etkisiyle yoğunluğu gün geçtikçe artan önemli bir tarihi ve ticari merkezdir. Çalışmada Aksaray Meydanı ve yakın çevresindeki ısı adası etkisi albedo, bitki örtüsü, geometri ve antropojenik ısı olmak üzere dört parametre üzerinden incelenmektedir. Alanın yüzey albedoları avwa (albedo viewer web application) matematiksel modeli kullanılarak hesaplanmakta ve mevcut alanın kentsel ısı adası oluşumuna etkisi değerlendirilmektedir. Alandaki bitki örtüsün etkisi İstanbul Büyükşehir Belediyesi tarafından hazırlanan renkli solar radyasyon haritalarıyla, geometri etkisi rüzgar analizleri ve arazi kesitleriyle, antropojenik ısı etkisi ise Çevre ve Şehircilik Bakanlığı’nın Aksaray Hava Kalitesi İzleme İstasyonu’ndan alınan verilerle incelenmektedir. Ayrıca bu dört parametre meydanın 2018 yılında tamamlanması planlanan kentsel tasarım uygulaması için de incelenerek, alandaki kentsel ısı adası etkilerinin azaltılmasına yönelik öneriler geliştirilmektedir. Elde edilen bulgulara göre, mevcut alandaki albedo değerleri 0.19 olarak belirlenerek ısı adası potansiyeli oluşturmaktadır. Aksaray Meydan Projesi ile albedo değerinin 0,22’ye çıkması öngörülerek meydan tasarımı ile alandaki ısı adası etkisi önlenememektedir. Alandaki mevcut bitki örtüsünün güneş radyasyonunu azaltıcı yönde etki ettiği görülse de, yeşil alanların doğal soğutma etkisi verimli bir şekilde kullanılmamaktadır. Geometri ve antropojenik ısı bulgularında ise alandaki ısı adası potansiyelini arttıracak büyüklükte bir etken tespit edilmemesine karşı, değerlerdeki artış gösteren eğilimler dikkate alınarak planlanan kentsel tasarım uygulaması için iyileştirme önerilmektedir.

Urban heat island become one of the most important problem in urban areas as a reflection of global warming in local scale last years. The term "heat island" describes built up areas that are hotter than nearby rural areas. Half of the world’s human population lives in urban areas. In the near future it’s expected that the global rate of urbanization will increase by 70% of the urban population by 2030, as urban agglomerations emerges and population migration from rural to urban areas continues. The negative impacts of urbanization is an increasing concern capturing the attention of people worldwide. Urbanization negatively impacts the environment mainly by the covering of the natural surfaces, the production of pollution and the modification of the physical and chemical properties of the atmosphere. Urban design is one of the primary practice and research tool to provide an environmentally friendly urban development. In this case, ecological parameters, especially energy consumption, should be taken into account in urban design practices, to ensure the balance of conservation and use of available resources in urban areas. An urban heat island is a city or metropolitan area that is significantly warmer than its surrounding rural areas due to human activities. Elevated temperatures from urban heat islands can affect a community’s environment and quality of life negatively. Some of these effects are increased energy consumption, elevated emissions of air pollutants, compromised human health and comfort, impaired water quality. According to increased energy consumption, elevated summertime temperatures in cities increase energy demand for cooling. Depending on compromised human health and comfort, increasing daytime temperatures, reducing nighttime cooling and higher air pollution levels associated with urban heat islands can affect human health by contributing to general discomfort, respiratory difficulties, heat cramps and exhaustion and heat-related mortality. According to impaired water quality, high surface temperatures of pavement and rooftops can heat stormwater runoff. Many communities are taking action to reduce urban heat islands. For example, US Environmental Protection Agency determined four main strategies for mitigating urban heat island effect: increasing tree and vegetative cover, installing green roofs, installing cool mainly reflective roofs and using cool pavements. Today, İstanbul, which is one of the fast-growing metropolitan city is under the pressure of rapid urbanization and population increase. In this thesis, mitigating strategies of urban heat island effects by urban design are investigated in Aksaray Square and surroundings in İstanbul. Aksaray is a neighborhood in Istanbul, which is a part of the district of Fatih. It also borders the neighborhood of Eminönü around the Pertevniyal Valide Sultan Mosque, with the intersection of major public transportation nodes. Aksaray has a composite appearance, with many historical xxii places, hotels and shops, mostly active in international trade. Between too many other reasons, the main reason Aksaray has been choosen as the study area, being located in the commercial and historical center of the city and having the most important transportation nodes is the primary ones for Aksaray to be a living square. Existence of Valide Sultan Mosque and commercial areas nearby makes this region and especially Aksaray Square an attractive center for the people. Also, there is an urban design project implementation of the square in 2018 and the effects of this urban design project to the area is evaluated in this study. In the scope of the poject, Aksaray Square and surroundings (the area from Valide Sultan Mosque to Murat Pasa Mosque and Zubeyde Hanım Park) has been designed as an integrated square as 60.851 m2 pedestrian area. Additionally, some of the urban blocks will be demolished and street pattern will be changed according to project. The studies on urban heat islands can be evaluated in three different sizes as macro, meso and micro scale in the literature. First group of the studies are made with high scale and satellite images and covering the entire city or surroundings. Second group of the studies, based on the comparison of data of meteorological stations in urban and rural areas, covering the entire city or a portion of the urban area. Finally, the third group of the studies are made with numerical models based on heat and energy calculations, mostly in building blocks or unit scale. This study is located in the third group based on the method and scope of the research. Purpose of the thesis, emphasizing the importance of urban design objectives and strategies, which is developed to reduce the heat island effect as an outcome of global climate change, that negatively affect the social environment and quality of life in urban areas . Objectives determined according to purpose of the thesis are;  determining the urban heat island effect by using urban design parameters.  developing urban design strategies to reduce the heat island effect, considering the factors that lead to the formation of heat islands such as geometry and materials etc.  predicting the effects of the urban design projects, that is planned to be implemented in the future, to the urban heat island. According to the hypothesis developed with respect to the aims and purposes; reducing the urban heat island effect, which occurs due to factors such as materials, geometry, pollution and affects negatively the social environment and quality of life in urban areas, with the urban design strategies developed for these factors. The urban heat island effect eximed depending surface albedo, vegetation, geometry and anthropogenic heat factors in the study area. First factor, the surface albedo, is calculated by albedo viewer web application (avwa) mathematical model, which is developed by Energy and Environmental Engineering Department, Kyushu University in Japan. The basic principle of the application is the detection of albedo values, which is affected to urban canopy layer through the urban form and solar radiation. The albedo vales of existing and planned urban blocks is calculated by avwa model. Albedo values are the most effective parameter in the formation of the heat island effect in urban areas. Changing in albedo value of 0.1, leads to 0.3-0.5˚C temperature changes in the urban areas. Therefore, calculated albedo values has a great importance in the evaluation of the heat island effect of the area According to the results, albedo value of the existing area calculates as 0,19 which shows an heat xxiii island potential in the study area. After the urban design project, this value is expected to be 0.22 which means, heat island potential decreases but hasn’t been removed by the urban design project of the square. Secondly, the effect of vegetation investigated from colored solar radiation maps which is prepared by İstanbul Metropolitan Municipality. Aksaray Square and surroundings have 0,66 hectares active and 1,7 passive green spaces. All of these green spaces, where trees and vegetation cover exists, has lower solar radiation than other regions in the area. However, the radiation values in the neglected green spaces were determined higher than other green areas. Depending on the results, trees and vegetation covers have been determined to have positive effects in reducing the urban heat island potential in the study area. Third factor, geometry is examined by wind analysis and sections of the area. Based on wind speed and direction anlysis and sections, urban canyon effect is evaluated in Aksaray Square and surroundings. As stated in the results, there is no area identified which blocks to the wind flow and forms the canyon effect. Finally, the effect of antropogenic heat is investigated from the tropospheric ozone datas which is taken from Aksaray Air Quality Monitoring Station of Environment and Urban Ministry. The tropospheric ozone, which release from motor vehicles and industrial activies, briefly anthropogenic activities, is one of the basic parameter in measuring anthropogenic heat. As reported by datas from 2010 to today, tropospheric ozone measured under 120 ppbv in the area, which is the threshold value. However, an increase have been identified 13% of the maximum value and 43% of the average value of tropospheric ozone, since 2010. Thus, precautions must be taken by determining the cause of the accelerated increase in tropospheric ozone values in the area. Urban design strategies have been developed to reduce the heat island effect in the area in addition to the urban design project of Aksaray Square. Three main design principle should be implement in Aksaray Square and surroundings to decrease urban heat island effect: using green or cool roofs, giving importance to the landscaping and green spaces, preferring cool pavements. Firstly, when the green or cool roof systems applied in all structures, albedo value will increase to 0.7 and urban heat island effect will be reduced in the range of 50-90% in the area. In this case, only roof arrangement in whole area will be effective in the elimination of the heat island effect by itself. Secondly, the priority should be given to landscaping while designing the proposed sites of the square. Because, increasing green areas of the sqaue will drop the temperature about 2-5˚C and improve the air quality. Also, edges of the grand boulevards and streets should be planted due to prevent anthropogenic heat and noise spread around from the traffic. Addionally, reforestation should be done to all of the streets and roads for avoiding the urban canyon effect. Finally, cool paving material should be used in pedestrian areas and parking lots which has high albedos. This will also reduce energy consumption about 30%. Based on the studies and obtained information; albedo values, vegetation cover, urban geometry and antropogenic heat factors are investigated according to the obtained quantitative and spatial data for identifying the potential of urban heat island, under the case study of Aksaray Square and surroundings. Hypothesis is verified with the data obtained from literature, mathematical model and analysis, and by using urban design strategies in urban areas, heat island effect can be eliminated.
Reducing The Urban Heat Island Effect By Urban Design Strategies: Aksaray Square Case
(Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
(M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2016
Keywords: kentsel tasarım; ısı adası; iklim değişikliği; aksaray meydanı; urban design; heat islands; climate change; Aksaray Square